Private equity in practice: commercial due diligence on a supplier for original equipment manufacturers - Bohle, Henning (2022)
This case elaborates the process and challenges of a commercial due diligence process on printed circuit board manufacturer Flex Voltage. It is a company producing and selling printed circuit boards to hearing aid manufacturers while engineering the components in close alignment with their customers. Printed circuit boards are used as connecting materials within almost every electrical item enabling control of electrical circuits, yet the range of Printed circuit boards varies widely depending on its use case. Due to many printed circuit board producers being in private ownership, this case aims to guide through the process of gaining detailed insights despite highly limited data availability in the field of private equity investments.